Spatial patterns in the global distributions of savanna and forest. Issue 7 (23rd April 2018) - Aleman, Julie C.; Staver, A. Carla
Abstract: Aim: The global distribution of biomes is not solely determined by climate. Top‐down processes, most notably fire, may substantially expand savannas into potentially forested areas. Here, we address an overlooked aspect of the existing literature: spatial patterns in savanna and forest distributions and the transitions between them, and whether current transitions could plausibly reproduce current distributions. Location: Tropical Africa and South America. Time period: 2000–2012. Major taxa studied: Biomes. Methods: Using remotely sensed tree cover and rainfall, we examined the distributions of savanna and forest and of transitions between the two. We examined forest gain directly, but because forest loss mostly reflects direct anthropogenic deforestation, we instead examined the proportion of forests experiencing one or more fires as an indirect proxy for potential conversion of forest into savanna. The effects of biome transitions on biome movements and distributions at continental scale were evaluated using a cellular automata model via simulation using observed decadal rates of transitions. Results: Although open‐ and closed‐canopy systems were both common at intermediate rainfall, they were strongly spatially segregated. So too were forest fires, which occurred mostly near their boundary with savannas, while forest encroachment of savanna was widespread. Simulations showed that observed transitions could not have produced current biome distributions. Main conclusions: Biome distributions in the tropics are not exclusively determined by climate (especially at intermediate rainfall), but are nonetheless strongly spatially structured. Current transitions between savanna and forest could not have reproduced their current distributions, suggesting that, historically, the spatial structure of transitions was probably different than it is today. While forest sub‐canopy fires are still spatially structured, forest encroachment of savannas may be much more widespread than it was in the past.